Prevalence and clinical characterisation of pregnant women with eating disorders. (27th January 2020) - Bye, Amanda; Nath, Selina; Ryan, Elizabeth G.; Bick, Debra; Easter, Abigail; Howard, Louise M; Micali, Nadia
Abstract: Objective: To estimate prevalence of lifetime and current eating disorders (ED) in a sample of pregnant women in South‐East London and to describe their sociodemographic and clinical characteristics. Method: Secondary analysis of data from a cross‐sectional survey. Using a stratified sampling design, 545 pregnant women were recruited. Diagnostic interviews were administered to assess lifetime and current ED, depression, anxiety, and borderline personality disorder. Data were extracted from maternity records to assess identification of ED in antenatal care. Estimates of population prevalence of ED were obtained using sampling weights to account for the stratified sampling design. Results: Weighted prevalence of lifetime ED was 15.35% (95% confidence interval [CI] [11.80, 19.71]), and current ED was 1.47% (95% CI [0.64, 3.35]). Depression, anxiety, and history of deliberate self‐harm or attempted suicide were common in pregnant women with ED. Identification of ED in antenatal care was low. Conclusions: Findings indicate that by early pregnancy, a significant proportion of pregnant women will have had ED, although less typically during pregnancy, and psychiatric comorbidity is common. Yet ED were poorly recognised in antenatal care. The findings highlight the importance of increasing awareness about maternal ED to improve identification and response to the healthcare needs of pregnant women with ED. Three key highlights: Weighted prevalence of lifetime eating disorders was 15.35% (95% CI [11.80, 19.71]), and current eating disorders was 1.47% (95% CI [0.64, 3.35]) in a UK inner‐city antenatal sample; however, eating disorders were poorly recognised in antenatal care. Depression, anxiety, and a history of deliberate self‐harm or attempted suicide are common amongst pregnant women with eating disorders. Findings highlight the clinical importance of increasing awareness about maternal eating disorders in maternity professionals to improve identification and response to the healthcare needs of pregnant women with eating disorders.